If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -9) = -8x + 44 Reorder the terms: -6(-9 + x) = -8x + 44 (-9 * -6 + x * -6) = -8x + 44 (54 + -6x) = -8x + 44 Reorder the terms: 54 + -6x = 44 + -8x Solving 54 + -6x = 44 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 54 + -6x + 8x = 44 + -8x + 8x Combine like terms: -6x + 8x = 2x 54 + 2x = 44 + -8x + 8x Combine like terms: -8x + 8x = 0 54 + 2x = 44 + 0 54 + 2x = 44 Add '-54' to each side of the equation. 54 + -54 + 2x = 44 + -54 Combine like terms: 54 + -54 = 0 0 + 2x = 44 + -54 2x = 44 + -54 Combine like terms: 44 + -54 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| x/((0.005-x)(2-4x)^4) | | 3/8+4/7= | | x+0.23x=258.30 | | x/((0.01-x)(4-4x)^4) | | 10+m=25 | | d-3=10 | | 43-4x=45*x-7 | | a+12=17 | | 2m(m-1)+3(1-m)=0 | | y=x^3-3x+2 | | 8e+9= | | 43-4x=45*x | | 43-4x=45*x/7 | | 43-4x=45*x^7 | | 12x^4-3x-2=0 | | 9+x*6=(14+x)*3 | | 100=3x^2+17x-20 | | 3(x+4)+2x=27 | | x^2-5.5x+1=0 | | 5+f=2f-3 | | (2w^2)+w-45=0 | | 80X=22400 | | Y=12x^2-11x+2 | | 100000×1/3 | | -x^2-12x-27=0 | | -23653.66987x^2+20.41309257x+794.6951483=0 | | 3x^8/9x^4 | | 98-5c=9c | | 12a+15b+9c=X(Aa+Bb+3c) | | -3+2y=13 | | 0=6x^2-14x+4 | | 3(6)-4y=10 |